Effect of different rest period after dynamic warm-up protocol on sprint performance among university football athletes/ Sylvester Jelani Gadoh - Gadoh, Sylvester Jelani (2019)
The purpose of this study is to investigate effect of different rest period after dynamic warm-up protocols on sprint performance among football athletes. Twenty university football athletes (21.70 ± 1.34 years, 63.79 ± 2.63 kilogram, 167.55 ± 3.27 centimetres) were divided into four group equally; DI (0 minute rest), D2 (5 minutes rest), D3 (10 minutes rest) and D4 (15 minutes rest) and had pre-test and post-test of 30 meters sprint test with three trials. There was significant effect for 0, 5 and 10 minutes rest period after dynamic warm-up protocol (p<.05) indicating an increase in speed performance. Thus, it may be suitable to use rest period between 0 to 10 minutes after dynamic warm-up protocols for football athletes use in game or training for a better speed performance.